Huge Left Atrial Aneurysm: First Case Report in Bangladesh - Fatema, Nurun Nahar; Prabhu, Sudesh (Cardiovascular Journal, 2021)
The left atrial aneurysm (LAA) is an extremely rare congenital malformation of the heart. It can be caused by congenital dysplasia of atrial muscle. It may result secondarily from severe mitral valvular disease. This is the first ever case of left atrial aneurysm in an 8 months old child of Bangladesh who was treated successfully and now leading a normal life after surgical resection. Cardiovasc j 2021; 14(1): 70-72